PERENCANAAN MUSEUM DESA DIGITAL DENGAN MENGGUNAKAN FRAMEWORK TPACK - Iryanti, Emi (Proceeding SENDI_U, 2015)
The museum has several benefits including learning resources, tourist destination which laterbecame one of the sources of income. Increased income source to trigger increased prosperitymoreover the museum is a museum village, can be a starting point increase in rural communitiesand reduce urbanization. With this objective, the village museum should be designed attractivelyso as to increase the interest of visitors. To facilitate researchers in formulating the desired inputand output , then the use of thought / idea of Koehler & Mishra that includes three elements,namely : content , pedagogy and technology . In terms of content will be differentiated by categorywhile in terms of pedagogy is represented by the evaluation / quiz at the end of each category andin terms of technology is the concept of different technologies based on predefined categories.keywords : digital village museum, TPACK framework, design